2001
DOI: 10.1002/ana.1014
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for digenic inheritance in a family with both febrile convulsions and temporal lobe epilepsy implicating chromosomes 18qter and 1q25-q31

Abstract: We report a clinical and genetic study of a French family among whom febrile convulsions (FC) are associated with subsequent temporal lobe epilepsy (TLE) in the same individual, without magnetic resonance imaging-identifiable hippocampal abnormalities. Linkage analyses excluded the loci FEB1 and FEB2, previously implicated in FC; the GEFS+1 locus responsible for generalized epilepsy with febrile seizures plus; and the locus implicated in lateral temporal lobe epilepsy. After scanning the entire genome, signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
50
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(56 citation statements)
references
References 32 publications
(32 reference statements)
3
50
2
Order By: Relevance
“…In most patients, seizures appear to be focal, mainly occurring during the first years of life and well controllable. Interestingly, in agreement with these data, Baulac et al [2001] reported a French family presenting with temporal lobe epilepsy and febrile convulsions, in whom a genome-wide scan demonstrated evidence for markers at 18qter.…”
Section: Discussionsupporting
confidence: 75%
“…In most patients, seizures appear to be focal, mainly occurring during the first years of life and well controllable. Interestingly, in agreement with these data, Baulac et al [2001] reported a French family presenting with temporal lobe epilepsy and febrile convulsions, in whom a genome-wide scan demonstrated evidence for markers at 18qter.…”
Section: Discussionsupporting
confidence: 75%
“…The gene for generalized epilepsy with FS plus, which is an epileptic syndrome characterized by FSs persisting beyond age 6 y and non-FSs, was identified as SCN1B, the gene coding for the accessory subunit ␤1 of the voltage-gated sodium channel (5,6). Digenic inheritance was suggested for pedigree segregating FSs and temporal lobe epilepsy and loci mapped to chromosome 1q and 18qter (32).…”
Section: Discussionmentioning
confidence: 99%
“…FTLE may be associated with febrile seizures [104][105][106][107][108] or MTS [108,109]. FTLE associated with febrile seizures has been linked to sodium channel SCN1A mutations [104].…”
Section: Genetic Predispositionmentioning
confidence: 99%